The mediating role of meaning at work in promoting teacher commitment and reducing burnout - Suyatno, Suyatno; Pambudi, Dholina Inang; Wantini, Wantini; Abdurrohim, Abdurrohim; Mardati, Asih (Frontiers in Education, 2022)
The influence of teachers' commitment and burnout on student learning outcomes and their performance requires astute research to identify the antecedent factors of these two variables. Commitment and burnout are peremptorily related to the positive and negative aspects of performance, respectively. Most of the previous research showed inconsistency, therefore, a new assay is needed to produce more convincing findings. This study aims to identify the antecedent variables of teachers' commitment and job burnout by using meaning at work as a mediating variable. Based on the random sampling technique, 304 respondents were selected among the teachers in private primary and secondary education levels in the East Kalimantan Province, Indonesia. A structural equation model (SEM) was used in the data analysis. The results showed that school support, self-actualization, and meaning at work were antecedent variables for teachers' commitment and burnout. The meaning at work also mediates the relationship between school support and self-actualization. Meanwhile, the remaining four mediating roles were not proven in this research. These findings offer a framework for principals to increase commitment and reduce teachers' burnout by increasing school support and self-actualization through meaning at work.